Retail Nation: Department Stores and the Making of Modern Canada - Belisle, Donica (UBC Press, 2011)
[This book] traces Canada's transformation into a modern consumer nation back to an era when Eaton’s, Simpson's, and the Hudson’s Bay Company fostered and came to rule the country’s shopping scene. Between 1890 and 1940, department stores revolutionized selling and shopping by parlaying cheap raw materials, business-friendly government policies, and growing demand for low-priced goods into retail empires that promised to meet citizens' needs and strengthen the nation. Some Canadians found happiness and fulfillment in their aisles; others experienced nothing more than a cold shoulder and a closed door. The stores' advertising and public relations campaigns often disguised a darker, more complicated reality that included strikes, union drives, customer complaints, government inquiries, and public criticism. This vivid account of Canadian department stores in their heyday showcases them as powerful agents of nationalism and modernization. But the nation that their catalogues and shopping experience helped to define - white, consumerist, middle-class - was more limited than nostalgic portraits of the early department store suggest. --Publisher's description. Contents: Rise of mass retail -- Creating modern Canada -- Fathers of mass merchandising -- Crafting the consumer workforce -- Shopping, pleasure, and power -- Working at the heart of consumption -- Criticizing the big stores. Includes bibliographical references (p. 274-292) and index.
Keywords: Consumption (Economics); Department stores; History; Retail trade